Math Anxiety and Financial Anxiety Predicting Individuals’ Financial Management Behavior - Xin, Ziqiang; Xiao, Huiwen; Lin, Gege (Depression and Anxiety, 2023)
Background. In managing finances, people need to process various financial texts containing math (e.g., amount of money and mathematical concepts) and financial information (e.g., funds and bonds). Such information could trigger anxiety related to math and finance; however, previous literature has rarely investigated the prediction role of contextual anxiety on financial management behavior. Therefore, the current study examined how math anxiety and financial anxiety are related to individuals’ financial management behavior assessed by self-report and objective observation, respectively. Methods. Study 1 investigated 186 employees with the math anxiety scale, financial anxiety scale, and financial management behavior scale to explore how math anxiety and financial anxiety predicted financial management behavior. Study 2 used a “choice/no choice” paradigm to observe how the high (n=50) and low (n=53) financial anxiety groups chose (or avoided) between a math task and a finance task (as a measurement of financial avoidance). Results. Study 1 showed that financial anxiety fully mediated the negative relationship between math anxiety and financial management behavior and the mediating effect size was −0.24, 95%CI=−0.34,−0.16. And compared to math anxiety (r=−0.24, p<0.01), financial anxiety (r=−0.45, p<0.01) was a stronger negative predictor of financial management behavior. Study 2 revealed that, compared to people with low financial anxiety, those with high financial anxiety were 2.75 times more likely to choose financial avoidance. Conclusions. People’s financial management behavior can be predicted by financial anxiety and math anxiety (especially the former), and the two types of anxiety seem to derive more from an irrational self-perception rather than actual ability. So, reducing financial anxiety and math anxiety should come first to motivate people to manage finances.